Electrical behavior of chemically grown lanthanum ferrite thin films - Ranieri, M. G.A. [UNESP] (2016)
Perovskite structured oxides are important functional materials often used for the development of modern devices. To extend their applicability, these materials need to be scalably and efficiently grown in the form of thin films. In this work, perovskite structured thin films of nanograined LaFeO3 (LFO) were chemically grown using polymeric precursors on Pt substrates. The thin films were characterized by X-ray diffraction, field-emission scanning electron microscopy, atomic force microscopy, and transmission electron microscopy. The electrical properties of the films were also measured. The homogeneous LFO thin films synthesized at a sintering temperature of 500 °C in 2 h contained grains with lateral dimensions of about 68 nm and 356 nm in thickness. The dielectric permittivity and dielectric loss measurements of the sample indicated only a slight dispersion in the frequency because of the lower two-dimensional stress in the plane of the film. The nanograined LFO semiconductor thin films showed a room temperature magnetic coercive field, which rendered them magnetically soft. The electrical characterization of the films, including temperature-dependent conductivity and thermopower confirmed p-type conduction and the mobility activation energy was measured to be 0.96 eV. A strong magnetization with a remnant magnetization of ∼60 emu/g was observed in the LFO films, indicating the uncompensated spin magnets moments of the Fe3+ ions.